Features of recording practices and communication during nursing handover: a cluster analysis - Nikos Rikos; Manolis Linardakis; Michael Rovithis; Anastas Philalithis (SciELO, 2018)
ABSTRACT Objective: To record and identify the characteristics of nursing handovers in a tertiary hospital. Method: Observational study. Twenty-two nurses participated in 11 nursing handovers in 2015/16, using a recorded audio system and an unstructured observation form. Hierarchical cluster analysis was performed. Results: Thirty characteristics were identified. The nursing handovers were based on the clinical status of patients, and all nurses obtained specialized scientific knowledge specific to the clinical environment. The information used was not based on nursing diagnoses and not in accordance with best nursing clinical practice. The following four clusters emerged among the 30 characteristics: 1) the use of evidence-based nursing practice, 2) the nonuse of evidence-based nursing practice and its correlation with strained psychological environment, 3) patient management and the clinical skills/knowledge of nurses, and 4) handover content, quality of information transferred and specialization. Conclusion: Multiple characteristics were observed. The majority of characteristics were grouped based on common features, and 4 main clusters emerged. The investigation and understanding of structural relations between these characteristics and their respective clusters may lead to an improvement in the quality of nursing health care services.